Struktur Politik dan Deradikalisasi Pendidikan Agama Bagi Anak Muda di Indonesia - Mohammad Iqbal Ahnaf (Jurnal Pendidikan Islam, 2013)
This paper addresses the issue of youth susceptibility to radicalization that has been a major concern since report finding suggesting a high number of youth support and participation in radical groups. Using political opportunity theory in social movement studies, this paper discusses the macro context of radicalization among youth. It shows that changes in the social and political landscape in Indonesia have motivated the shift of focus of Islamist movement toward mobilization at the social level as an alternative to failing political activism in parliament. In addition to this macro context, this paper illustrates the forms of social millie in schools that are critical to radicalization in schools. It concludes that the key to radicalization in school does not primarily lay in a religious teaching curriculum but on condition and activities outside the classroom that allows the transmission of radical narratives among students.